1999
DOI: 10.1139/cjm-45-6-472
|View full text |Cite
|
Sign up to set email alerts
|

Stress tolerance in a yeast lipid mutant: membrane lipids influence tolerance to heat and ethanol independently of heat shock proteins and trehalose

Abstract: The response of a yeast unsaturated fatty acid auxotroph, defective in delta 9-desaturase activity, to heat and ethanol stresses was examined. The most heat- and ethanol-tolerant cells had membranes enriched with oleic acid (C18:1), followed in order by cells enriched with linoleic (C18:2) and linolenic (C18:3) acids. Cells subjected to a heat shock (25-37 degrees C for 30 min) accumulated trehalose and synthesized typical heat shock proteins. Although there were no obvious differences in protein profiles attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Sterols for example, long time relegated as passive metabolites modulating the membrane structure, play an important role as primary sensors of environmental stresses by adjusting the fluidity of the plasma membrane to such perturbations [46,47]. The cellular lipid metabolism is highly susceptible to hypoxia since the biosynthesis routes for the most essential lipids - ergosterol and fatty acids - require molecular oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Sterols for example, long time relegated as passive metabolites modulating the membrane structure, play an important role as primary sensors of environmental stresses by adjusting the fluidity of the plasma membrane to such perturbations [46,47]. The cellular lipid metabolism is highly susceptible to hypoxia since the biosynthesis routes for the most essential lipids - ergosterol and fatty acids - require molecular oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Mutation in other fungi has been correlated with altered cell wall assembly (Claverie-Martin et al, 1988;Ram et al, 2004); as well as changes in wall thickness (Claverie-Martin et al, 1988;Osherov and May, 2001), conidial surface features (Jahn et al, 1997), and composition of fatty acids (e.g. increased fatty acid unsaturation in plasma membrane as stress tolerance decreases) (Swan and Watson, 1999;Chatterjee et al, 2000). The mutants DWR 031 and 033, on the other hand, had high tolerance for both irradiations types, indicating that cell wall and membranes are more important to heat protection (improving thermotolerance) than UV-B radiation.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of ethanol S. cerevisiae, which contains only mono-unsaturated fatty acids, showed an increase in palmitoleic acid (C16:1D9), whereas a decrease in fatty acid desaturation was found in K. lactis, which contains monoenoic, dienoic and trienoic fatty acids. It has also been reported that S. cerevisiae enriched with C18:3 by fatty acid supplementation showed sensitivity to ethanol, which may be attributable to membrane damage associated with increases in membrane fluidity (Swan and Watson, 1999).…”
Section: Response Of M Rouxii Cells Grown At Different Phases To Ethmentioning
confidence: 94%